Osteolytic metastases from a pheochromocytoma presenting as multiple limb lameness and joint swelling in a dog: a case report - Swindell, Madeleine; Bolton, Timothy A.; Powers, Cassandra M.; Novotny, Ladislav; Jarvis, Jack; Murakami, Masahiro (Frontiers in Veterinary Science, 2025)
Clinical signs due to distant bony metastasis from a malignant pheochromocytoma are rare in dogs, with the majority of reported cases presenting as single-limb lameness. This case report describes a 6-year-old neutered male mixed-breed dog presenting with multiple limb lameness and joint swelling that occurred over 3 weeks. Computed tomography revealed a mass in the right adrenal gland with extensive intrathoracic, intra-abdominal, and skeletal metastases. Because of the poor prognosis, the dog was humanely euthanized. A postmortem examination revealed a primary neoplasm of the right adrenal gland with metastases affecting the contralateral adrenal gland, kidneys, lungs, liver, and bones of the appendicular and axial skeletons. Immunohistochemistry confirmed a metastatic neuroendocrine carcinoma of the right adrenal gland, consistent with a pheochromocytoma. This case is a unique presentation of polyostotic metastases from a pheochromocytoma and emphasizes the importance of including this tumor in the differential diagnosis of dogs presenting with symptoms identical to those of polyarthritis.